Gender diversity, renewable energy consumption, and financial performance: a study of Indonesian energy companies - Adityaningrum, Fatimah; Sunarjo, Wenti Ayu; Meliza, Meliza (Institute of Computer Science (IOCS), 2024)
This study aimed to examine the effect of gender diversity and renewable energy consumption on financial performance, gender diversity on renewable energy consumption, and mediation of renewable energy consumption in the relationship between gender diversity and financial performance in the perspective of stakeholder theory. The population of this study was energy sector companies listed on the Indonesia Stock Exchange in 2020-2022, with total samples obtained based on purposive sampling technique were 58 observation data. The results of PLS-SEM analysis using WarpPLS 8.0 software showed that gender diversity had a significant negative effect on renewable energy consumption and financial performance, while renewable energy consumption had a significant positive effect on financial performance. Furthermore, renewable energy consumption was not proven to significantly mediate the effect of gender diversity on financial performance